2015
DOI: 10.1128/aac.00105-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Moxifloxacin-Containing Regimens in Pathologically Distinct Murine Tuberculosis Models

Abstract: dIn the recently concluded REMox-TB trial, two 4-month moxifloxacin-containing regimens did not meet the criteria for noninferiority compared to the current 6-month first-line regimen to treat tuberculosis (TB). Despite the disappointing result, this phase 3 clinical trial provides a rare opportunity to gauge the predictive accuracy of the nonclinical models used to support regimen development. In parallel with the REMox-TB trial, we compared the efficacy of the same three regimens against chronic TB infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
12
30
1
Order By: Relevance
“…The limit of detection was 3 CFU/organ. greater therapeutic efficacy and lower relapse rates achieved in this study with the regimen in which moxifloxacin replaced isoniazid than with the standard regimen are consistent with previous reports (5)(6)(7)(8). De Groote et al demonstrated that replacement of isoniazid by moxifloxacin in the standard regimen gave rise to a 63% disease relapse rate (6).…”
Section: Discussionsupporting
confidence: 92%
“…The limit of detection was 3 CFU/organ. greater therapeutic efficacy and lower relapse rates achieved in this study with the regimen in which moxifloxacin replaced isoniazid than with the standard regimen are consistent with previous reports (5)(6)(7)(8). De Groote et al demonstrated that replacement of isoniazid by moxifloxacin in the standard regimen gave rise to a 63% disease relapse rate (6).…”
Section: Discussionsupporting
confidence: 92%
“…This is disappointing and context is provided by a comparison with earlier trials in table 1. Post hoc reports have suggested that the outcome could have been predicted by a different mouse model: a chronic TB low-dose inhalation infection in BALB/c mice and in C3HeB/FeJ mice, which unlike other strains develop caseous lung lesions and may better resemble human TB [52]. A statistical explanation is that the best of the phase IIb studies reported a hazard ratio for the time to culture conversion for the moxifloxacin-containing regimen, as compared with the standard regimen, of 1.73 (95% CI 1.15-2.60), suggesting a shorter duration regimen might be possible [36].…”
Section: Observations On the Outcome Of Phase III Treatment-shorteninmentioning
confidence: 99%
“…The later-generation fluoroquinolones (FQs), particularly moxifloxacin, have shown a great deal of promise in animal models (2) and are currently recommended by the WHO as second-line drugs for the treatment of drug-resistant TB (3); however, they are not currently licensed for the treatment of drug-sensitive TB. Recently, three separate clinical trials evaluated a potential role for FQs in shortening the duration of therapy for drug-sensitive TB from the current 6 months to 4 months, an important goal aimed at simplifying TB therapy and reducing default rates, which contribute to the emergence of drug resistance (4)(5)(6).…”
mentioning
confidence: 99%